2015
DOI: 10.1007/s10854-015-3238-2
|View full text |Cite
|
Sign up to set email alerts
|

AC conductivity properties of annealed In2S3 film deposited by spray technique

Abstract: In 2 S 3 thin film was prepared by chemical spray pyrolysis technique onto clean soda-lime glass substrate. Indium chloride and thiourea were used as reagents. This film was sealed into Pyrex tube at a pressure of 10 -6 Torr and then annealed at 673 K for 3 h. The film was characterized by means of X-ray diffraction (XRD), atomic force microscope (AFM) and by impedance spectroscopy measurements. XRD spectra show that In 2 S 3 film is polycrystalline with a cubic phase and preferentially oriented towards (400).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Such a procedure is especially adapted for combinatorial and fast screening investigations [372][373][374] and can be excellently combined with microbeam and nanobeam GISAXS (µ/nGISAXS) [33,24,375]. For practical applications, it is of course important to establish the nanostructure-function relationship of the installed layers [376], e.g. correlate AC/DC resistivity, optical properties etc.…”
Section: Photovoltaicsmentioning
confidence: 99%
“…Such a procedure is especially adapted for combinatorial and fast screening investigations [372][373][374] and can be excellently combined with microbeam and nanobeam GISAXS (µ/nGISAXS) [33,24,375]. For practical applications, it is of course important to establish the nanostructure-function relationship of the installed layers [376], e.g. correlate AC/DC resistivity, optical properties etc.…”
Section: Photovoltaicsmentioning
confidence: 99%
“…Indeed, only a few reports have been carried out on impedance spectroscopy of these semiconductor thin films. For example, in our previous works we investigated the ac conductivity properties of annealed In2S3 film [19] as well as the electrical conductivity of nickel doped In2S3 thin films deposited on glass substrates by spray technique [1]. Seyam [20] and Timoumi et al [21] reported the dependence of ac conductivity on frequency of thermally evaporated In2S3 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large number of cationic vacancies [24,25], the indium sulfide may be acting as a sink for tin incorporation. Owing to these important properties, a number of techniques have been used to synthesize In 2 S 3 such as spray pyrolysis [26][27][28][29][30][31][32][33], ultrasonic dispersion [34], chemical bath deposition [35], physical vapor deposition [36] [29,[37][38][39] and correlated to growth parameters, structural and optical properties. Therefore, in the present work, In 2 S 3 :Sn 1 % thin films prepared by spray pyrolysis technique and annealed at 400°C have been investigated in term of their structural, morphological and optical properties.…”
Section: Introductionmentioning
confidence: 99%